Combining SDLC Method and ITIL Framework by Involving Auditors - Hani Rahmani; Erna Hikmawati (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2020)
The framework that provides best practice in IT service management is called IT Infrastructure Library (ITIL). The IT service management leads to the management of a service, this service is generated through the system development process. Each system has a different scale, characteristics, requirements, types, and properties but has the same stage in its development, that is by implementing the System Development Life Cycle (SDLC) Software developers on IT projects must implement SDLC by selecting a particular model process. But many IT development teams do not pay attention to software management frameworks or standards so that they will experience difficulties in planning, reporting work results, monitoring, controlling, etc., especially when all personnel in the team don’t have sufficient experience. It would be better if every software house company and IT Consultant applies the general framework and standardization so that the software development process will be more directed and produced high quality services. In conducting the SDLC process, an accountant is needed, in this case the auditor who has a role as an information provider in describing business processes in a company activity, the auditor also plays a role as controller that ensuring the system is in accordance with accounting regulations, and accountants also act as checker of the system so that the auditors must involved in the initial design of a system. The application of ITIL in the SDLC process will have an impact on the ease of the auditor in carrying out the duties.